PENYELESAIAN SENGKETA WAKAF DALAM HUKUM POSITIF (UIN Sunan Kudus, 2014)
Waqf property in principle are the property of the people, as suchbenefits must also be felt by the people and therefore at the level of the waqfproperty is ideally collective responsibility to maintain it’s exist.Indonesian state has a Muslim majority society. This conditioncertainly makes the problem of managing endowments, become a very urgentproblem and very vulnerable. In addition, problems sometimes arise seizureof waqf land ownership rights between the heirs wakif nadzir even there is aperson who has dared to be against the law to transfer or assign ownership toanother party. Those problems need to be addressed as well as law enforcementboth litigation and non-litigation order berkepastian law, justice and legalexpediency. Indonesia is a country of law as in Article 1 (3) of the Constitutionof the Republic of Indonesia (UUDNRI) 1945, so that all activities in ourcountry governed by law.Dispute resolution based on traditional endowment Indonesianpositive law is: Non-Litigation. (A). Peace and Alternative Dispute Resolution(ADR). The legal basis of dispute resolution outside of court can be deliveredas follows: Article 3, paragraph (1) of Law No. 14 of 1970, Article 1851 ofthe Civil Code, Article 1855 of the Civil Code, Article 1858 of the Civil Code,alternative dispute resolution is only regulated in one article, namely Article6 of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution.(B). Procedures and dispute settlement procedures of Article 62 of Law No.perwakafan 41/2004 explains: perwakafan dispute settlement be reachedthrough negotiation to reach an agreement, if the dispute resolution referredto in subsection (1) does not succeed, the dispute can be resolved throughmediation, arbitration, or court. Article 62 of Law No. 41/2004 explains thatin solving the problems of the waqf property to first prioritize the attitude ofdeliberations to reach a consensus. Litigation: In the context of endowments,the Institute for Religious Courts through Article 49 of Law No. 7 of 1989as amended by Act Number 3 of 2006 on the Religious Courts. EndowmentsAct No. 41 of 2004, there are criminal provisions, which is still limited targetNazdhir and Officer Deed of Pledge Waqf. This is explained in Article 67paragraph (1) and paragraph (3).